Pengembangan Instrumen Penilaian Tes Tertulis pada Materi Membaca Pemahaman - Afni Yunita; Desi Sukenti (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The research entitled "Development of Written Test Assessment Instruments on Reading Comprehension Materials (Folk Story Texts) at MAN 1 Pekanbaru". The purpose of the study was to determine the development process, validity, and reliability of the written test assessment instrument on reading comprehension materials for folklore texts at MAN 1 Pekanbaru. This type of research is research and development (R&D) or research and development that aims to produce an assessment product that is used to assess the written test task of reading students' understanding that meets the criteria of validity and reliability. The instrument development used Sugiyono's research and development model which was modified into 8 steps. Sources of research data are Indonesian language subject educators at MAN 1 Pekanbaru and students of class X IPA 1 and IPA 2. Data collection techniques are using test techniques and non-test techniques (interviews, document analysis, questionnaires). The results of the study said that the development stage of the written test assessment instrument on the reading comprehension material of folklore texts started from: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision. , (6) trial, (7) product revision, and (8) final product. While the results of the validity of the student questions, totaling 30 questions, it can be seen that there are 2 questions that cannot be used or discarded. While the reliability of the written reading comprehension test assessment instrument shows that, (1) The literal reading comprehension type has a very high correlation coefficient level with an average of 0.842, (2) The interpretation reading comprehension type has a very high correlation with an average of 0.834 (3 ) the type of critical reading comprehension has a high correlation coefficient with an average of 0.677, (4) and the type of reading comprehension application obtains an average of 0.716 with a high correlation coefficient. So that it can be seen that students have good abilities in working on questions on reading comprehension materials of folklore texts